Implementasi Sistem Informasi Manajemen Berbasis Aplikasi Madina Sehat Di SMA Madina Citra Insani - Helda Yusfarina Anggraini; Suratman Suratman (Program Studi Manajemen Pendidikan Islam, Fakultas Tarbiyah dan Ilmu Keguruan, IAIN Ponorogo, 2023)
The current development of information technology will have a significant impact on the world of education. Technological advances are so rapid and unavoidable that management information systems play a role that is very necessary for the progress of an educational institution. Schools are required to be able to keep up with the ever-evolving pace of the times in order to avoid being left behind in technological developments. SMA Madina Citra Insani is a high school that utilizes a management information system in managing data through the use of the Madina Sehat Application. This research was carried out with the aim of describing the implementation of a management information system based on the Madina Sehat application, identifying supporting and inhibiting factors, as well as the impact that occurs on the use of the Madina Sehat application as a support for the implementation of the management information system at SMA Madina Citra Insani. The article was written using a qualitative descriptive approach method with a type of field research. Data collection was carried out using observation, interviews and documentation techniques. Then the data that has been collected is analyzed using the Miles, Huberman, and Saldana models. The validity of the data was tested using data triangulation techniques. The results of the research show that the implementation of a management information system based on the Madina Sehat application at SMA Madina Citra Insani is used by the school's Nakes Team (Health Personnel) to disseminate information about students' health conditions every day to school stakeholders. Using this application allows students to get two types of services, namely internal health services and external health services, while the provision of services in this case is tailored to the students' needs.